Ghost horses - Hill, Pamela Smith (New York : Holiday House, 1996)
Sixteen-year-old Tabitha, the daughter of a preacher who believes science is Satan's work, longs to study at a university and dig for dinosaur bones, but in South Dakota at the end of the nineteenth century such ambitions are discouraged.
Keywords: Sex role -- Fiction; Paleontology -- Fiction; Fathers and daughters -- Fiction; South Dakota -- Fiction